2016
DOI: 10.3892/etm.2016.3019
|View full text |Cite
|
Sign up to set email alerts
|

Surgical resection of vasoactive intestinal peptideoma with hepatic metastasis aids symptom palliation: A case report

Abstract: Vasoactive intestinal peptideoma (VIPoma) is a rare pancreatic endocrine tumor associated with a well-defined clinical syndrome characterized by watery diarrhea, hypokalemia and metabolic acidosis. In adults, VIPoma is most commonly found in the pancreas, with 80% of the tumors occurring in the body and tail and 20% occurring in the pancreatic head. VIPomas can represent a significant diagnostic challenge due to their nonspecific clinical presentation, which can result in the misdiagnosis of a VIPoma as anothe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 13 publications
0
4
0
Order By: Relevance
“…Of these, 15 patients (15/30, 50%) were male and 15 patients (15/30, 50%) were female [Figure 2]. [23456789101112131415161718192021222324252627282930]…”
Section: Resultsmentioning
confidence: 99%
“…Of these, 15 patients (15/30, 50%) were male and 15 patients (15/30, 50%) were female [Figure 2]. [23456789101112131415161718192021222324252627282930]…”
Section: Resultsmentioning
confidence: 99%
“…Both studies and case reports have reported the successful use in patients with VIPomas of the control of the symptoms of the hormone-excess state by using: tyrosine kinase inhibitor sunitinib[47, 49]; liver directed therapies including TACE/TAE[70, 100, 173, 174, 184, 185]; radioembolization[70, 150], RFA [81, 83, •186, 187, 188]; by increasing the dosage of octreotide/Lanreotide in refractory cases[185] and the use of cytoreductive surgery[100, 102, 134, 158, 160, 174, •186, 189]. …”
Section: Summary Of Recent Advances In Management Of Specific Hormmentioning
confidence: 99%
“…Somatostatin analogues (SSAs) inhibit VIP secretion and are used to control symptoms[ 15 ]. Somatostatin is a peptide that reduces the secretion of an ample set of hormones[ 50 ]. Various studies on functional NETs have shown that controlling hormone levels is crucial to reduce patients’ morbidity and mortality[ 51 ].…”
Section: Treatment/managementmentioning
confidence: 99%